Penerimaan Masyarakat Terhadap Modul Sosialisasi Standar, Pedoman dan Manual (SPM) (Studi Kasus Sosialisasi Standar, Pedoman dan Manual (SPM) Sertifikat Laik Fungsi (SLF) Bangunan Gedung di Provinsi Sumatera Barat dan Daerah Istimewa Yogyakarta) - Rosa, Yulinda (Jurnal Sosial Ekonomi Pekerjaan Umum, 2014)
One of the factors which influences on improving the quality of housing and residential communities is the lack of understanding on the SPM. It can be improved through well-planned socialization programs. In order to optimize the results of socialization of SPM SLF Building with module systems, an evaluation is needed to determine the level of public acceptance. Survey research methods with consideration of sampling technique (purposive) are used in this study. The data collected are priomary ones, by using a questionnaire instrument as well as a discussion or direct interviews with the respondents. Descriptive analysis method and correlation analysis method are used in this research. Socialization of SPM SLF buildings implemented with the module system is well-received by society, providing varying levels of influence on the public perception ranging from low, medium and high level, depending on prior knowledge of the respondent of the two provinces and any material provided. Socialization SPM SLF Building by modules system can be implemented through the development of the concepts of knowledge transfer through adult education, taking into account the required elements in communication.